REFINE: A Randomized Trial Comparing Cyclosporine A and Tacrolimus on Fibrosis After Liver Transplantation for Hepatitis C. Issue 3 (23rd January 2014) - Levy, G.; Villamil, F. G.; Nevens, F.; Metselaar, H. J.; Clavien, P.‐A.; Klintmalm, G.; Jones, R.; Migliaccio, M.; Prestele, H.; Orsenigo, R.; ,
<x xml:space="preserve">Abstract</x> REFINE was a 12‐month, prospective, open‐label study in 356 patients receiving de novo liver transplantation for hepatitis C virus (HCV) cirrhosis, randomized to cyclosporine A (CsA) or tacrolimus with (i) no steroids, IL‐2 receptor antibody induction and mycophenolic acid, or (ii) slow steroid tapering. The primary analysis population based on availability of liver biopsies comprised 165 patients (88 CsA, 77 tacrolimus). There was no difference in the primary endpoint, fibrosis stage ≥2 at 12 months, which occurred in 63/88 CsA‐treated patients (71.6%) and 52/77 tacrolimus‐treated patients (67.5%) (odds ratio [OR] 1.11; 95% CI 0.56, 2.21; p = 0.759). Similarly, no significant between‐group difference occurred at month 24 (OR 1.15; 95% CI 0.47, 2.80; p = 0.767). Among steroid‐free patients, fibrosis score ≥2 was significantly less frequent with CsA versus tacrolimus at month 12 (7/37 [18.9%] vs. 16/38 [42.1%]; p = 0.029). HCV viral load was similar in both the tacrolimus‐ and CsA‐treated cohorts. Mean blood glucose was significantly higher with tacrolimus from day 15 onward. Biopsy‐proven acute rejection, graft loss and death were similar. These results showed no differences in posttransplant HCV‐induced liver fibrosis between patients treated with CsA or tacrolimus in steroid‐containing regimens, whereas CsA in steroid‐free protocols was associated with reduced severity of fibrosis progression at 1 year posttransplant.